2016
DOI: 10.1163/22134808-00002516
|View full text |Cite
|
Sign up to set email alerts
|

Which Direction Is up for a High Pitch?

Abstract: Low- and high-pitched sounds are perceptually associated with low and high visuospatial elevations, respectively. The spatial properties of this association are not well understood. Here we report two experiments that investigated whether low and high tones can be used as spatial cues to upright for self-orientation and identified the spatial frame(s) of reference used in perceptually binding auditory pitch to visuospatial ‘up’ and ‘down’. In experiment 1, participants’ perceptual upright (PU) was measured whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In order to disclose the role of vestibular and proprioceptive sensory information on perceived verticality, much research has used a simple paradigm in which verticality is judged when tilted in the roll-plane. In this context, uni- and multisensory contributions have been investigated by focusing on the subjective visual vertical [SVV; (1114)], the subjective haptic vertical [SHV; (1517)] the subjective auditory vertical (18) and the interaction of visual and haptic sensory information on perceived verticality (16). The advantage of this methodology is that it provides an indirect measurement of the perceptual readout of vestibular and proprioceptive sensory information signaling body orientation relative to gravity.…”
Section: Introductionmentioning
confidence: 99%
“…In order to disclose the role of vestibular and proprioceptive sensory information on perceived verticality, much research has used a simple paradigm in which verticality is judged when tilted in the roll-plane. In this context, uni- and multisensory contributions have been investigated by focusing on the subjective visual vertical [SVV; (1114)], the subjective haptic vertical [SHV; (1517)] the subjective auditory vertical (18) and the interaction of visual and haptic sensory information on perceived verticality (16). The advantage of this methodology is that it provides an indirect measurement of the perceptual readout of vestibular and proprioceptive sensory information signaling body orientation relative to gravity.…”
Section: Introductionmentioning
confidence: 99%
“…At 4-5 months infants are able to detect synchrony between visual and acoustic stimuli [40,41], to make associations between sounds and changes in the direction of a movement [42,43], to match faces and voices (e.g., [44,45]) and to recognize similarities between the common rhythmic structures, tempo, and duration of auditory and visual events ( [46][47][48]; see [49], for a review). Within this cross-modal context it is also well known that humans spontaneously describe auditory pitch spatially (e.g., [50][51][52]). The correspondence between symmetrical acoustic and visual patterns addressed in the present study is based precisely on this spatial correspondence: the vertical distance between the dots in the visual stimuli corresponds to the distance between the notes in the acoustic stimuli which indicates the pitch (see Appendix A).…”
Section: Introductionmentioning
confidence: 99%
“…Yet our study demonstrates that pitch correspondences, typically studied with tones and music, generalize to human voice pitch. Moreover, whereas previous studies using tonal stimuli have used broad pitch ranges spanning 200-8000 Hz (see, e.g., Cabrera et al, 2005;Carnevale & Harris, 2016;Mudd, 1963;Parise et al, 2014;Pratt, 1930), we have demonstrated that frequency-elevation mapping is elicited with voice pitch manipulations of only 20-40 Hz at pitch centers of 100-250 Hz (although this degree of manipulation is still an order of magnitude larger than the just-noticeable differences for pitch detection in similar vocal stimuli; see Re et al, 2012). In addition, our results show that the influence of pitch on spatial perception goes beyond localizing sounds in space, but also affects performance in an indirect spatial task, and one that has ecological relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several previous studies reported that the relative position of a listener's head and torso to the sound stimulus can affect how pitch is mapped to space (e.g., Algazi, Avendano, & Duda, 2001;Middlebrooks & Green, 1991;Roffler & Butler, 1968). In their recent study, Carnevale and Harris (2016) demonstrated that people used ascending-and descending-pitch scales as spatial orientation cues, indicating which way was spatially Bup^and which way was Bdown,r espectively, when lying on their sides versus sitting upright. However, static high-or low-pitched tones (1200 vs. 200 Hz) had no effect on participants' perceptions of their own orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation